Mechanism‐Guided Design and Synthesis of a Mitochondria‐Targeting Artemisinin Analogue with Enhanced Anticancer Activity. (6th October 2016) - Zhang, Chong‐Jing; Wang, Jigang; Zhang, Jianbin; Lee, Yew Mun; Feng, Guangxue; Lim, Teck Kwang; Shen, Han‐Ming; Lin, Qingsong; Liu, Bin
Abstract: Understanding the mechanism of action (MOA) of bioactive natural products will guide endeavor to improve their cellular activities. Artemisinin and its derivatives inhibit cancer cell proliferation, yet with much lower efficiencies than their roles in killing malaria parasites. To improve their efficacies on cancer cells, we studied the MOA of artemisinin using chemical proteomics and found that free heme could directly activate artemisinin. We then designed and synthesized a derivative, ART‐TPP, which is capable of targeting the drug to mitochondria where free heme is synthesized. Remarkably, ART‐TPP exerted more potent inhibition than its parent compound to cancer cells. A clickable probe ART‐TPP‐Alk was also employed to confirm that the attachment of the TPP group could label more mitochondrial proteins than that for the ART derivative without TPP (AP1). This work shows the importance of MOA study, which enables us to optimize the design of natural drug analogues to improve their biological activities.